Comparison of the Safety, Tolerability, and Pharmacokinetics of Fidaxomicin in Healthy Japanese and Caucasian Subjects - Oshima, Hiroyuki (Clin Drug Investig, 2015)
BACKGROUND AND OBJECTIVES: Fidaxomicin treatment of Clostridium difficile infection is known to produce minimal systemic exposure, as the antibacterial (antibiotic) remains primarily in the gut. In this randomized, double-blind, placebo-controlled study, the safety, tolerability, and pharmacokinetics of single and multiple ascending doses of fidaxomicin were evaluated in healthy Japanese and Caucasian subjects. METHODS: Thirty-six healthy subjects were randomly assigned in a 3:1 ratio to receive either fidaxomicin or placebo. Cohort 1 (100 mg) and Cohort 2 (200 mg) comprised 12 Japanese subjects each and Cohort 3 (200 mg) comprised 12 Caucasian subjects. Subjects received a single dose of the study drug on Day 1 and received multiple doses for 10 days after a wash-out period. RESULTS: After multiple 200 mg dosing of fidaxomicin, both mean maximum plasma concentrations (C(max)) in Japanese (8.7 ± 5.3 ng/mL) and Caucasian (7.0 ± 3.7 ng/mL) subjects and the area under the concentration–time curve (AUC) were higher in Japanese subjects (58.5 ± 36.7 ng·h/mL) than in Caucasian subjects (37.6 ± 15.7 ng·h/mL), although variation in both groups was large. The mean fecal concentrations of fidaxomicin in Japanese and Caucasian subjects were 2669 and 2181 μg/g, respectively. The possibly study drug-related adverse events were diarrhea (n = 1), feeling hot (n = 1), and hypersomnia (n = 2), which were mild in severity. CONCLUSIONS: In both Japanese and Caucasian subjects, fidaxomicin demonstrated similarly minimal systemic absorption, and was mainly excreted in feces. Fidaxomicin was safe and well-tolerated in all subjects.